Counter-apocalyptic beginnings: cosmoecology for the End of The World. Issue 1 (1st January 2021) - Savransky, Martin
ABSTRACT: Departing from Aimé Césaire's striking proposition that The End of the World is the only thing in this world that is worth beginning, this article sets out to explore some of its implications as a counter-apocalyptic gesture that renders apocalypse an immanent event: the end of some world in this world. Probing the speculative force of Césaire's counter-apocalyptic proposition, the article suggests that it can trouble one of the more insidious powers of Anthropocene stories: the way in which, by conflating the end of Euro-American extractive ways of living with the end of everything as such, such stories reduce the plural interplay of immanent values which sustain divergent modes of living and dying well to sheer matters of "survival, " thereby determining what is vital to life, and how lives worth living and deaths worth living for are to be defined. Weaving together philosophical experimentation with a story of other modes of living and dying inside and despite ecological turmoil, the article takes up the notion of "cosmoecology" as a way of experimenting with plural value-ecologies of living and dying on a heterogenous Earth.